Flame Retardant and Mechanical Properties of Modified Paper Using Inorganic Salts for Packaging Applications - Youssef, Ahmed M.; Mohamed, Ola A.; El-Samahy, M.; Kader, Amal H. Abd-El; Pichtec, Luhac (Journal of Research Updates in Polymer Science, 2015)
The paper sheet prepared from unbleached rice straw containing different concentration of inorganic salts, that work as flame retardant additives (Lithium hydroxide one hydrate (LiOH.1H2O), Magnesium hydroxide (Mg (OH)2. 15H2O), aluminum sulphate (Al2(SO4)3) and calcium carbonate (CaCO3)) were investigated using horizontal burning test against flame retardant. Also, the prepared paper sheets were characterized using scanning electron microscope (SEM), thermal gravimetric analysis (TGA) and Infrared spectroscopy (IR). Furthermore, the water absorption was determined. In addition, the mechanical properties (breaking length, tear factor and burst factor) of the prepared paper sheet were evaluated. Correspondingly, the physical (structure and mechanical) properties of the prepared paper sheet were enhanced in terms of tensile, tear factor and water absorption. Also, delaying firing process will help in protecting the materials from burning, saving many of economic effect. So the prepared paper sheet can be used for different industrial applications especially in packaging applications.